The Role of Parents in Shaping Children's Religious Character Amidst the Challenges of the Digital Era - Revandi, Abdul; Bakhruddin, Mukhammad; Hayumuti, Hayumuti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This research aims to analyze the role of parents in shaping children's religious character in the digital era. As technology advances, parents are expected to serve as primary educators who provide role models and instill moral values in their children. The rapid development of digital technology presents challenges, such as exposure to content that contradicts religious values and reduced direct interaction between parents and children. Therefore, active parental involvement is crucial to ensuring that children develop a strong religious character. This study employs a qualitative descriptive method, with data collected through interviews and observations. The findings indicate that good parenting, motivation, and the habitual practice of religious values in daily life significantly influence children's character development. Children who receive intensive guidance from their parents tend to have a better understanding and practice of religious values than those who receive less attention. However, challenges such as parental busyness and limited time for direct religious education hinder this process. A lack of parental attention can obstruct the internalization of religious values. Thus, parents must recognize their responsibility in shaping their children's character and make efforts to remain actively involved in their education. With proper guidance, children can grow into individuals who are not only intellectually capable but also exhibit commendable morals and ethical behavior.